Parental Communication in Building Mental Resilience for Children with Thalassemia - Melanie Shava Verellia; Ahmad Muhaimin; Putri Citra Hati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Thalassemia is a chronic disease that not only impacts the physical condition of the child, but also on psychological and social aspects. The role of parents through interpersonal communication is an important factor in forming children's mental resilience to face these conditions. This study aims to find out how parental communication in building mental resilience of children with thalassemia and parents' efforts to overcome obstacles in communicating with children. This study uses a qualitative approach with a descriptive method. Data collection was conducted through in-depth interviews with parents and secondary data to reinforce the findings. Data analysis is carried out by identifying, grouping, and interpreting data in the context of parent-child communication. This study uses the framework of Symbolic Interaction Theory to understand how the meaning constructed by parents through communication contributes to children's mental resilience. The results of the study show that the role of parents in building the mental resilience of children with thalassemia and become a guideline for related agencies to increase awareness of the physical, psychological, and social conditions of chronic disease sufferers.